2019
DOI: 10.1111/jcmm.14462
|View full text |Cite
|
Sign up to set email alerts
|

Metformin mediates induction of miR‐708 to inhibit self‐renewal and chemoresistance of breast cancer stem cells through targeting CD47

Abstract: Breast cancer stem cells (BCSCs) have been considered responsible for cancer progression, recurrence, metastasis and drug resistance. However, the mechanisms by which cells acquire self‐renewal and chemoresistance properties are remaining largely unclear. Herein, we evaluated the role of miR‐708 and metformin in BCSCs, and found that the expression of miR‐708 is significantly down‐regulated in BCSCs and tumour tissues, and correlates with chemotherapy response and prognosis. Moreover, miR‐708 markedly inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 35 publications
2
72
0
Order By: Relevance
“…In another study, miR-708 induced repression of the WNT/βcatenin signaling pathway in BCSCs, causing inhibition of selfrenewal and chemoresistance in these cells. miR-708 was shown to directly bind the CD47 gene regulating the expression of this molecule and the tumor-associated macrophage-mediated phagocytosis (162).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionmentioning
confidence: 99%
“…In another study, miR-708 induced repression of the WNT/βcatenin signaling pathway in BCSCs, causing inhibition of selfrenewal and chemoresistance in these cells. miR-708 was shown to directly bind the CD47 gene regulating the expression of this molecule and the tumor-associated macrophage-mediated phagocytosis (162).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionmentioning
confidence: 99%
“…12,16 CD44 has multiple spliced isoforms and heavy glycosylation, which is involved in tumor cell migration in prostate cancer 27 and breast cancer. 28 Kim et al found that hepatocellular carcinoma patients with low expression of CD44 expressed a significantly better disease-free survival rate compared to those with higher CD44 29 and found that CD44 expression was an independent factor associated with survival. 30 Lina et al demonstrated that upregulation of CD44 as well as the variant isoforms can promote the activation induced by EGFR downstream signaling pathways.…”
Section: Dovepressmentioning
confidence: 99%
“…Characteristics of included studies are presented in Table 3. All articles were published between 2011 and 2019 and were written in English [33][34][35][36]. Studies have been carried out on two types of cancers: breast cancer [33,34,36] and pancreatic cancer [35].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All articles were published between 2011 and 2019 and were written in English [33][34][35][36]. Studies have been carried out on two types of cancers: breast cancer [33,34,36] and pancreatic cancer [35]. The studies were conducted in the USA (n = 1) [35], Spain (n = 1) [36], Japan (n = 1) [34] and in China (n = 1) [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation